Studies on Gandhi - Patil, V.T. (ed.) (New Delhi, 1983)
The present study is a scientific and systematic assessment of the theory and practice of Gandhism, its socio economic and political impact and its contemporary relevance. The papers presented in this volume seek to throw light on the different dimensions of Gandhi's contribution to modern political and social thought. There is in it a common theme which centres around a well-studied effort to illuminate the various facets of Gandhian thought with a rare insight. Some of the papers bring out the contradictions in Gandhian thinking which others clearly attribute to the inherent coherence and unity in Gandhian thought and practice. The analysis and interpretations of different aspects of the Gandhian phenomenon in this study will be of interest to scholars and policy makers in India and abroad.
Keywords: Gandhi M.K.